Uploading the ancestors: Experiments with digital Buddhist altars in contemporary Japan. Issue 7 (9th August 2019) - Gould, Hannah; Kohn, Tamara; Gibbs, Martin
Abstract: Domestic Buddhist altars have long provided symbolically and materially rich media for venerating the dead in Japan. However, as Japanese household structures and funerary rites are unsettled in the contemporary era, Buddhist altars ( butsudan ) are rapidly being reinvented and digitalized. In this article, we describe the new technologies harnessed in butsudan production, the sensory experiences they offer, and their abilities to both reform and reinforce traditional networks of ancestral obligation. Despite promising death rituals that are more personal, secular, and affordable, the development of digitally enhanced material memorialization is still very much a work in progress in Japan.